Patient Satisfaction in Child Welfare Centres at Dhaka Cantonment - Rahman, Irtika; Alam, Md Zulfikkar; Uddin, Abu Noman Mohammed Mosleh (Bangladesh Armed Forces Medical Journal, 2025)
Background: Patient satisfaction metrics are expected to become more and more significant in the movement to hold healthcare providers more accountable. This study's objective is to evaluate patient satisfaction in Dhaka cantonment's child care institutions. Methods: This descriptive type of cross sectional study was carried out in six Child Welfare Centres (CWCs) of Dhaka Cantonment, aimed to determine the satisfaction of patients regarding the availability, accessibility and behavior of staffs of the CWCs. One hundred fifty patients were interviewed by the researcher himself for a duration of 1" September to 31 December 2011. Results: Study finding disclosed that overall satisfaction level among the respondents were 62% and 7.3% were dissatisfied as such most of the respondents were satisfied with the current services offered by the Child Welfare Centres. However, it also showed there are some gray areas that need to be improved among which is also 'the waiting time' as maximum respondents (61.3%) waited for 21-40 mins to see a doctor. Mean waiting time was 29.77 ± 11.65 min. Patient as new case (12%) opined their dissatisfaction about waiting time. In regards to long waiting time, maximum respondents (75.30%) opined that their waiting time increased due to patient load and 12.70% opined for unavailability of medicine. Result of the study revealed that maximum (86.70%) respondents gave their opinion that doctors spent 5-10 mins with them and about 90% were satisfied about attention paid by the doctors to them. Regarding the satisfaction while on consultation with doctor, more than 25% of the respondents stated that their prescription was not properly explained to them by the doctor. More than 96% of the respondents stated that no. of nurses, paramedics & health workers were adequate. Maximum 71.30% respondents were satisfied about the behaviour of the staffs. The mean age of the respondents was 22.10 ± 10.21 years. Majority of the respondents (50.70%) were in the age group of 21-30 years. Maximum (86.0%) of the respondents were female and it was revealed that the females were more (78%) satisfied than male patients. More than 56%) of the respondents were literate, 67.3% were housewives and average monthly income was 17020.00 TK. Conclusion: The results of this study provide insights into how patients evaluate their care and, in turn, provide avenues for improving patient satisfaction. Bangladesh Armed Forces Med J Vol 57 No (2) December 2024, pp 29-35